The diabetic retina–brain axis hypothesis in diabetic cognitive impairment: from pathophysiological mechanisms to therapeutic implications - Zhang, Luofan; Zhang, Lerong; Wen, Haoyang; Wu, Sixian; Yu, Hanbo; Zhao, Lingyan; Li, Guiping (Frontiers in Endocrinology, 2026)
Diabetic cognitive impairment (DCI) is a frequent complication of diabetes that significantly reduces the quality of life of elderly patients and substantially increases the societal health–care burden. Recent epidemiological investigations have demonstrated that the severity of diabetic retinopathy (DR) is independently associated with a greater risk of cognitive dysfunction. To clarify the relationship between ocular and cerebral comorbidities in diabetes, this paper proposes the diabetic retina–brain axis hypothesis. By reviewing barrier dysfunction, neuroinflammation, and oxidative stress, we systematically present evidence that supports the involvement of the retina–brain axis in DCI and highlight the shared mechanisms that underlie retinal and cerebral damage in diabetes. Therapeutic strategies that target the retina–brain axis, such as hypoglycemic agents, antioxidants and neuroprotective interventions, provide benefits for retinal health and cognitive function. Investigating the mechanisms underlying this axis offers important insights for early diagnosis, prevention and treatment of DCI. Consequently, this research can guide the development of more effective interventions, for example by informing the use of sodium–glucose cotransporter 2 (SGLT2) inhibitors to protect both retinal microvasculature and neuronal integrity. Future research should prioritize elucidating the pathways of information transmission between the retina and the brain, and clarifying the molecular and cellular basis of these processes. This will provide theoretical support for the development of cross–organ collaborative protection strategies.